Peran Dinas Koperasi Usaha Mikro Perindustrian Dan Perdagangan Dalam Penanganan Dampak Pandemi Covid-19 Pada Usaha Mikro Di Kabupaten Gresik - Aziza Nur Auliya; Lukman Arif (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
The Covid-19 pandemic has had an impact on health and the national economy. At the economic level, one of the sectors that has been affected is micro enterprises, resulting in a decline in the welfare of business actors and the threat of bankruptcy. Therefore, actors are needed to solve these problems, one of which is the Micro Business Office. The purpose of this study was to determine the role of the Industry and Trade Micro Business Cooperative Service in handling the impact of the Covid-19 pandemic on Micro Enterprises in Gresik Regency. The research method used is descriptive qualitative. Data obtained through interviews, observation, documentation and literature study. The data analysis technique used in this study was interactive with the stages of data collection, data condensation, data presentation and conclusion drawing. The results show that the role of the Koperindag Office has carried out its role well in handling the impact of the Covid-19 pandemic on Micro Enterprises in Gresik Regency. Based on the results of field analysis, the role of Diskoperindag refers to its role as a facilitator, regulator and catalyst.